2015
DOI: 10.1111/mcn.12198
|View full text |Cite
|
Sign up to set email alerts
|

Stigma as a barrier to treatment for child acute malnutrition in Marsabit County, Kenya

Abstract: Acute malnutrition affects millions of children each year, yet global coverage of life-saving treatment through the community-based management of acute malnutrition (CMAM) is estimated to be below 15%. We investigated the potential role of stigma as a barrier to accessing CMAM. We surveyed caregivers bringing children to rural health facilities in Marsabit County, Kenya, divided into three strata based on the mid-upper arm circumference of the child: normal status (n = 327), moderate acute malnutrition (MAM, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…There are also additional barriers to access of other child health care services including limited time available and workload constraints of caregivers. Feelings of shame and discomfort at health clinics have also been reported by mothers of malnourished children in Marsabit County [9]. Pregnant women consume restricted diets with the belief that they will have easier delivery.…”
Section: Food Insecuritymentioning
confidence: 99%
“…There are also additional barriers to access of other child health care services including limited time available and workload constraints of caregivers. Feelings of shame and discomfort at health clinics have also been reported by mothers of malnourished children in Marsabit County [9]. Pregnant women consume restricted diets with the belief that they will have easier delivery.…”
Section: Food Insecuritymentioning
confidence: 99%
“…including their rights to receive respectful, dignified and humane care during growth monitoring (United Nations General Assembly, 1948, 1993. An association between the stigma of malnutrition and children's access to health care has also been reported in different contexts (Bliss, Njenga, Stoltzfus, & Pelletier, 2016;Howard & Millard, 1997;Mull, 1991;Nayar, Stangl, De Zalduondo, & Brady, 2014). The attitudes of health workers that were reported in the current study highlight the need to insist that health care providers separate their preconceived schemas from their professional duties.…”
Section: Naming and Shaming Of Mothers And Their Poorly Growing Babiesmentioning
confidence: 99%
“…Earlier studies of malnutrition in Marsabit County has concluded that social stigma connected with malnourished children is an important reason why mothers do not seek help for malnutrition. 13 We did not investigate this in our study, but we may suggest that increased general awareness on nutrition initiated by the establishment of mother support groups might contribute to reduce the stigma, and as such lower the threshold for mothers to seek help at health care facilities.…”
Section: Discussionmentioning
confidence: 87%